THE RELATIONSHIP BETWEEN BULLYING BEHAVIOR AND SELF EFFICACY IN STUDENTS - Aninda Nur Haliza; Azzahra Julia Nadina; Kenya Janesa Liandri; Radi Ubaidillah; Wahyu Agung Hidayatullah; Indah Lestari (Journal of Psychology and Social Sciences, 2023)
Bullying has become a global problem that is often encountered and faced by many people, especially teenagers, both as perpetrators of bullying and victims of bullying behavior. Bullying is a form of behavior that occurs repeatedly by means of physical harm and mentally carried out by a child or a group of children against other children. Bullying incidents faced by adolescents can have an impact on adolescent self-efficacy. Self-efficacy is the ability of a person or individual in completing tasks or problems so that they can achieve goals in overcoming obstacles experienced. Adolescents with high self-efficacy have the confidence and ability to solve problems with effective performance control. This research was conducted with the aim of seeing whether there is an influence between bullying behavior and self-efficacy in fourth semester students at the psychology faculty of Uin Raden Fatah University, Palembang. This study also uses a quantitative method with survey techniques, namely filling out questionnaires by giving several questions online to 38 respondents. There were 8 male respondents and 30 female respondents with an age range of 18-22 years. The respondents taken were 4th semester students of the Faculty of Psychology at UIN Raden Fatah Palembang. The results of this study indicate that the relationship between bullying behavior and self-efficacy is very significant and interconnected, which in Table 1.1 shows that between bullying behavior and self-efficacy there is a correlation coefficient (r) of 0.496 with a significance of 0.002. This research is strengthened by research conducted by Laurensia, Jenita Serangana et al (2021) showed the significance between bullying behavior and self-efficacy in adolescents. These results were supported by findings showing that 55 (27.5%) respondents received low bullying treatment and high self-efficacy, and 73 (36.5%) respondents received high bullying treatment and low efficacy.